Effect of a group medical clinic for veterans with diabetes on body mass index. (September 2019) - Eisenberg, Adva; Crowley, Matthew J; Coffman, Cynthia; Edelman, David
Objective: To assess the impact of a group medical clinic designed for patient with type 2 diabetes mellitus and hypertension on body mass index. Methods: Using data from a randomized trial of 239 veterans with type 2 diabetes mellitus, we performed a secondary analysis using analysis of covariance mixed models to explore the effect of a 12-month group medical clinic intervention on change in body mass index vs. usual care. In an exploratory subgroup analysis, we compared change in body mass index between treatment arms stratified by whether patients had >0.5% reduction in hemoglobin A1c at 12 months. Results: Baseline body mass index was 33.5 kg/m 2 . At 12 months, there was no significant difference in change in body mass index between treatment arms (estimate=−0.02, 95% CI −0.51 to 5.05; P = 0.94); body mass index increased by approximately 0.20 points in both groups. There was also no significant difference in change in body mass index between treatment arms by whether or not patients had >0.5% reduction in hemoglobin A1c (estimate=−0.14, 95% CI −1.21 to −0.92; P = 0.79). Discussion: Improved glycemic control was not associated with improved body mass index in the group medical clinic intervention. Given their positive effects on other outcomes, group medical clinics for patients with type 2 diabetes mellitus may be more beneficial if focus is shifted towards weight loss.